Experimental and Numerical Analysis of Condensation Heat Transfer and Pressure Drop of Refrigerant R22 in Minichannels of a Printed Circuit Heat Exchanger - Shilin Li; Zhongchao Zhao; Yanrui Zhang; Haijia Xu; Weiqin Zeng (Energies, 2020)
A Printed Circuit Heat Exchanger (PCHE) is a type of highly complete and efficient heat exchanger that consists of numerous mini/micro-channels and has been successfully applied to the Liquefied Natural Gas (LNG) regasification project. During the research presented in this paper, the condensation flow and heat transfer performance of the R22 in PCHE hot side minichannels are analyzed via experiments and numerical simulations, respectively. A liquid nitrogen–R22 experimental loop is established to examine the pressure difference and heat transfer coefficient of R22 in the minichannels of the PCHE hot side. The inlet pressures of the R22 range from 0.5 MPa to 0.65 MPa, the mass flux values are changed from 10.52 <semantics>kg<mtext> </mtext>m−2s−1</semantics> to 109.42<semantics><mtext> </mtext>kg<mtext> </mtext>m−2s−1</semantics>, and the inlet temperatures vary from 273 K to 289 K. The differences between experiments and simulations are analyzed by comparing the experimental values of the Nusselt number (Nu) and the friction pressure gradient with the numerical ones. Furthermore, the influences of pressure and mass flux on the Nu, as well as the friction pressure gradient, are analyzed in depth through condensation flow regimes to explore the underlying mechanism giving the results.